Novel electrochromic materials of PANI-TiO2 hybrid - Phua, Si Lei. (2009)
Nowadays, intensive interest has been drawn to the development of derivatives of polyaniline (PANI) in order to enhance its spectro-electrochemical properties. In order to improve its electrochromic contrast, we has successfully prepared PANI-TiO2 hybrids in which inorganic metal oxide was covalently bonded to aniline groups on the macromolecular chains. The organic-inorganic hybrid composites are expected to provide synergetic effects on electrochromic properties of the device. The structures of the hybrid systems are characterized using FTIR, TGA, WAXD and SEM/EDX analysis. Meanwhile, the spectro-electrochemical properties, cyclic voltammetry behavior, coloration efficiency and response times of the devices are studied. The results reveal that PANI has been grafted onto TiO2 using N-[3-(trimethoxysilyl propyl)aniline] as cross-linking agent. The hybrid systems exhibit enhanced optical contrast and coloration efficiency than that of PANI. This can be attributed to electron-drawing ability of TiO2 that leads to more accessible doping sites and higher ionic conductivity as well as higher electrochromic contrast than PANI. This innovative approach can be further investigated to develop multicolored electrochromism in organic-inorganic hybrid systems.